AGRICULTURAL FOOD ORIENTATION UNDER THE CONDITIONS OF THE CORONAVIRUS PANDEMIC - Botirova Rahima Abdujabborovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article explores the need and directions for strengthening the food orientation of agriculture in the context of the impact of the coronavirus pandemic.